2019
DOI: 10.1002/nsg.12052
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Mapping of Shallow Rock Salt at Borabue, Northeast Thailand

Abstract: In the northeast of Thailand, many swamps and lakes show evidence of rock salt dissolution, with attendant environmental problems due to saline groundwater and soil salinization. The knowledge of the depth and structure of the rock salt would be useful to achieve a better understanding of the impact of its dissolution on the environment and to facilitate effective land management strategies. Geophysical methods can provide key subsurface information. Four seismic refraction profiles and three electrical resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is suggested that faulting controls flow diversions of the Mekong River, rather than salt tectonics, because fault traces are evident in the older rock formations of the Laos region, rather than the younger rock salt formations. While the Mahasarakham evaporite formation is widely distributed at various depths across northeast Thailand, salt movements usually form structures of circular shape (Sarntima et al, 2019) rather than the long lineaments that are found in the northeast Khorat plateau.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that faulting controls flow diversions of the Mekong River, rather than salt tectonics, because fault traces are evident in the older rock formations of the Laos region, rather than the younger rock salt formations. While the Mahasarakham evaporite formation is widely distributed at various depths across northeast Thailand, salt movements usually form structures of circular shape (Sarntima et al, 2019) rather than the long lineaments that are found in the northeast Khorat plateau.…”
Section: Discussionmentioning
confidence: 99%